PERLINDUNGAN ANAK DI DESAPAKRAMAN RENON DENPASAR - Tary Puspa, Ida Ayu (Institut Hindu Dharma Negeri Denpasar, 2018)
The purpose of a marriage according to the view of Hinduism is to get suputra children who can save their ancestors from hell, so in a Hindu family it is expected to be born to a son who is suputra namely a virtuous, knowledgeable, and wise child. Thus, planning to build a spiritual and spiritual family can be realized. To realize a prosperous family, each family member has an obligation, among others, to protect his children. Parents must protect their children from all the distress that will happen to them and protect them from the influence of globalization so that children can look at their future well. That is what causes Pakraman Village to make child protection a protection if there is a child who is lawful